Synthesis of Temperature and Light Sensitive Copolymers with Controlled Aggregation during Phase Transitions. Issue 22 (3rd October 2019) - Ding, Lan; Zhang, Pengfei; Fu, Congcong; Yin, Jialin; Mao, Yongwang; Liu, Na; Li, Shihua; Yang, Chunying; Zhao, Ronghui; Deng, Kuilin
Abstract: Two thermosensitive copolymers of acrylates (PMP/PEP) and a thermo/light sensitive copolymer of acrylate with acrylamide (PMABz) are synthesized via a ring‐opening reaction and subsequent radical polymerization using a facile one‐pot method. The lower critical solution temperature (LCST) of PMP and PEP shows a dependence on the content of the structural unit and can be easily tuned to 18–35 °C by mercaptoethanol‐mediated control of the molecular weight. The isomerization of PMABz can be reversibly induced by alternating irradiation at 365 nm to produce the cis form and at 254 nm to produce the trans form. The LCST of cis ‐PMABz (40.3 °C) is significantly higher than that of trans ‐PMABz (37.8 °C) because of its higher hydrophilicity. Furthermore, the particle size of aggregated PMABz can be controlled from 665 nm (for the cis form) to 996 nm (for the trans form) during the heating run. After quenching the PMABz solution, PMABz particles have repeating patterns, such as leaf veins or hollow containers, indicating their potential applicability. Abstract : The synthesis of thermosensitive, photosensitive copolymers by the copolymerization and regulating the LCSTs by M n are described. In contrast to trans ‐PMABz, the more hydrophilic cis ‐PMABz shows a higher LCST, and cis ‐PMABz forms the smaller and uniform particles in the heating solution. Cis ‐ trans ‐PMABz particles present a leaf vein‐like or hollow container‐like appearance due to the synergistic thermo/photosensitivity on quenching.